Correlative 3D characterization of hierarchical zeolite structures linking nano X-ray tomography and 360° electron tomography - Drobek, Dominik; Apeleo Zubiri, Benjamin; Wirth, Janis; Englisch, Silvan; Weissenberger, Tobias; Schwieger, Wilhelm; Spiecker, Erdmann (European Microscopy Congress 2020, 2021)
In catalysis, the available total surface area for active sites is of utmost importance and the intraparticle pore space of a single particle has to be designed accordingly. In addition, the interparticle pore space, determining the packing density of a particle network, is also critical for catalytic applications. MFI-type zeolite particles exhibit such a structured pore system and can serve as support frameworks for catalytic applications. Applying multiscale Nano-X-ray tomography (Nano-CT) and 360° electron tomography (ET) reveals the complex morphology of a single MFI-type zeolite particle and even larger agglomerations of these particles can be analyzed in detail [1].
Keywords: 360° electron tomography; 3D; correlative microscopy; hierarchial material; nano X-ray tomography

Correlative Laboratory Nano-CT and 360° Electron Tomography of Macropore Structures in Hierarchical Zeolites - Apeleo Zubiri, Benjamin; Wirth, Janis; Drobek, Dominik; Englisch, Silvan; Przybilla, Thomas; Weissenberger, Tobias; Schwieger, Wilhelm; Spiecker, Erdmann (Advanced Materials Interfaces, 2020)
Hierarchical pore structures exhibit morphological features on several length scales, which govern important materials properties in catalysis, such as catalytic activity, diffusivity or selectivity. Correlative tomography offers unique opportunities for a comprehensive and scale-bridging 3D characterization of such complex pore morphologies, which is crucial to further optimize materials design and synthesis routines. This study explores the capabilities of correlative 360° electron tomography (ET) and lab-based nano X-ray computed tomography (Nano-CT) enabling 3D analyses of volumes of up to (60 µm)³ with down to nm resolution, as demonstrated for zeolite particles with embedded macropores. By first applying the two techniques to the same particle the higher resolution and fidelity of ET are used to improve the segmentation of pore space in the Nano-CT reconstruction. Extended statistical relevance and access to interparticle pore space are obtained from reconstructions of larger particle agglomerates, using the large-field-of-view mode of the Nano-CT. The presented correlative approach enables real space analyses of important pore characteristics for comparison with complementary pore characterization techniques. Moreover, by investigating samples from different stages of the synthesis, 360°-ET and Nano-CT provide unique insights into the formation mechanism of porous materials, as demonstrated for the steam-assisted crystallization of the macroporous zeolite particles.
CRIS-Team Scopus Importer:2020-10-16
Keywords: 360° electron tomography; correlative microscopy; hierarchical pore structure; nano X-ray tomography; phase contrast Nano-CT

Coupled ptychography and tomography algorithm improves reconstruction of experimental data - Kahnt, Maik; Becher, Johannes; Brueckner, Dennis; Fam, Yakub; Sheppard, Thomas; Weissenberger, Tobias; Wittwer, Felix; Grunwaldt, Jan-Dierk; Schwieger, Wilhelm; Schroer, Christian G. (Optica, 2019)
Three-dimensional (3D) x-ray microscopy by ptychographic tomography requires elaborate numerical reconstructions. We describe a coupled ptychography-tomography reconstruction algorithm and apply it to an experimental ptychographic x-ray computed tomography data set of a catalyst particle. Compared to the traditional sequential algorithm, in which ptychographic projections are reconstructed to serve as input for subsequent tomographic reconstruction, the coupled ptychography-tomography algorithm reconstructs the 3D volume with higher spatial resolution over a larger field of view. Coupling the data from different projections improves the overall reconstruction, and the ptychographic sampling in individual projections can be coarsened beyond the point of overlap between neighboring scan points, still leading to stable reconstructions. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-11-01

Coupled ptychography and tomography reconstruction of experimental data - Kahnt, Maik; Becher, Johannes; Brueckner, Dennis; Fam, Yakub; Sheppard, Thomas; Weissenberger, Tobias; Wittwer, Felix; Grunwaldt, Jan-Dierk; Schwieger, Wilhelm; Schroer, Christian G. (ACTA CRYSTALLOGRAPHICA A-FOUNDATION AND ADVANCES, 2021)
CRIS-Team WoS Importer:2022-04-01

Hierarchical MFI type zeolites with intracrystalline macropores: The effect of the macropore size on the deactivation behaviour in the MTO reaction - Weissenberger, Tobias; Reiprich, Bastian; Machoke, Albert; Klühspies, Katharina; Bauer, Juergen; Dotzel, Ralf; Casci, John L.; Schwieger, Wilhelm (Catalysis: Science and Technology, 2019)
Hierarchically structured ZSM-5 catalysts have been prepared using different sized mesoporous silica particles as the sacrificial template, resulting in zeolite crystals with different sized intracrystalline macropores but very similar zeolitic characteristics such as crystallinity, chemical composition, and acidic and textural properties. This set of catalysts was used to investigate the effect of intracrystalline macropores on the deactivation behaviour of ZSM-5 catalysts in the conversion of methanol to olefins (MTO). The catalytic tests showed that the incorporation of macropores was very beneficial in improving the catalyst lifetime in the MTO reaction. This improved performance was correlated to the reduced coke formation during the reaction, likely a result of the enhanced transport of reactants and products in the zeolite crystals due to the well-interconnected macropores. Also worth mentioning is the effect of the dimensions of the additional macropores on the rate of coke formation. Increasing the macropore size by a factor of two led to a decrease in coke formation and consequently a two times longer catalyst lifetime.
CRIS-Team Scopus Importer:2019-07-02

Hierarchical ZSM-5 Catalysts: The Effect of Different Intracrystalline Pore Dimensions on Catalyst Deactivation Behaviour in the MTO Reaction - Weissenberger, Tobias; Machoke, Albert; Bauer, Juergen; Dotzel, Ralf; Casci, John L.; Hartmann, Martin; Schwieger, Wilhelm (ChemCatChem, 2020)
Abstract: We present the effect of different combinations of intracrystalline pore systems in hierarchical ZSM-5 zeolites on their performance as MTO catalysts. We prepared ZSM-5 zeolites with additional intracrystalline mesoporous, intracrystalline macropores and a novel ZSM-5 type zeolite with intracrystalline meso and macropores. The catalytic results showed that both used catalysts with mesopores and macropores exhibited three times longer catalyst lifetime compared to a conventional catalyst. However, TGA analysis of the deactivated catalysts showed much larger coke content in the mesoporous catalyst than in the macroporous catalyst. Consequently, macropores predominantly led to reduced coke formation rate while additional mesopores predominantly enhanced the resistance against deactivation by coke. Combining both intracrystalline meso and macropores in one catalyst lead to a tenfold increase in catalyst lifetime. Besides the effect on the catalyst lifetime there was also a strong effect of the additional pore systems on the selectivity of the catalysts. The catalysts containing mesopores showed reduced selectivity to short chain olefins and increased selectivity to larger hydrocarbons in comparison to the catalysts without a mesopores system.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Heterogeneous catalysis; hierarchical materials; Mesoporous materials; nanostructures; Zeolites

Hierarchy concepts: classification and preparation strategies for zeolite containing materials with hierarchical porosity - Schwieger, Wilhelm; Machoke, Albert; Weissenberger, Tobias; Inayat, Amer; Selvam, Thangaraj; Klumpp, Michael; Inayat, Alexandra (Chemical Society Reviews, 2016)
'Hierarchy' is a property which can be attributed to a manifold of different immaterial systems, such as ideas, items and organisations or material ones like biological systems within living organisms or artificial, man-made constructions. The property 'hierarchy' is mainly characterised by a certain ordering of individual elements relative to each other, often in combination with a certain degree of branching. Especially mass-flow related systems in the natural environment feature special hierarchically branched patterns. This review is a survey into the world of hierarchical systems with special focus on hierarchically porous zeolite materials. A classification of hierarchical porosity is proposed based on the flow distribution pattern within the respective pore systems. In addition, this review might serve as a toolbox providing several synthetic and post-synthetic strategies to prepare zeolitic or zeolite containing material with tailored hierarchical porosity. Very often, such strategies with their underlying principles were developed for improving the performance of the final materials in different technical applications like adsorptive or catalytic processes. In the present review, besides on the hierarchically porous allzeolite material, special focus is laid on the preparation of zeolitic composite materials with hierarchical porosity capable to face the demands of industrial application.

Layer-like FAU-type zeolites: A comparative view on different preparation routes - Reiprich, Bastian; Weissenberger, Tobias; Schwieger, Wilhelm; Inayat, Alexandra (Frontiers of Chemical Science and Engineering, 2020)
The creation of intergrown layer-like zeolite crystals is one route to form hierarchical zeolites. Faujasite-type (FAU-type) zeolites are among the industrially most important zeolites and the implementation of hierarchical porosity is a promising way to optimise their catalytic and adsorptive performance. After a short general survey into routes for the preparation of hierarchical pore systems in FAU, we will review the currently existing strategies for the synthesis of FAU with layer-like morphology. Those strategies are mainly based on the presence of morphology modifying agents in the synthesis mixture. However, a very recent approach is the synthesis of layer-like FAU-type zeolite crystals assembled in an intergrown manner in the absence of such additives, just by finely adjusting the crystallization temperature. This additive-free preparation route for layer-like FAU, which appears very attractive from an ecological as well as economic point of view, is highlighted in this review. Concluding, a comparison, including powder X-ray diffraction, scanning and transmission electron microscopy, nitrogen physisorption and elemental analysis, between conventional FAU and three layer-like FAU obtained by different synthesis routes was carried out to show the structural, morphological and textural differences and similarities of these materials. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-01-21
Keywords: FAU; hierarchical zeolite; layer-like morphology

MFI Type Zeolite Aggregates with Nanosized Particles via a Combination of Spray Drying and Steam-Assisted Crystallization (SAC) Techniques - Machoke, Albert; Arias, Aurina Martinez; Baracchini, Giulia; Rubin, Michael; Baser, Hasan-Hüseyin; Weissenberger, Tobias; Dittmeyer, Roland; Weber, Alfred; Hartmann, Martin; Schwieger, Wilhelm (Catalysts, 2023)
Hydrothermal synthesis is the state-of-the-art technique for the preparation of zeolites and related porous solids. However, when it comes to the preparation of nanosized zeolites, this technique is limited by low yields, separation problems and high amounts of waste. In this work, we utilized the strengths of a combination of spray drying and steam-assisted crystallization (SAC), also known as dry gel conversion, to reduce these problems. At spray drying temperatures between 300 and 400 degrees C, it was possible to convert all the amorphous material via SAC into zeolite particles without extra addition of template. Kinetic studies of SAC revealed that about 4 to 8 days are needed to achieve the formation of a 100% crystalline product. The newly formed crystalline phase was crystallized on the surface of the nanosized zeolites and led to a slight increase in the primary particle size while the macroscopic morphology of the spray-dried aggregates was preserved. This work demonstrates that the combination of spray drying and SAC are useful tools in supplementing the hydrothermal synthesis of nanosized zeolites.
CRIS-Team WoS Importer:2023-04-14
Keywords: spray drying; steam-assisted crystallization; zeolites

Micro/Macroporous System: MFI-Type Zeolite Crystals with Embedded Macropores - Machoke, Albert; Beltran, Ana M.; Inayat, Alexandra; Winter, Benjamin; Weissenberger, Tobias; Kruse, Nadine; Guettel, Robert; Spiecker, Erdmann; Schwieger, Wilhelm; Spiecker, Erdmann (Advanced Materials, 2015)
Zeolite crystals with an embedded and interconnected macropore system are prepared by using mesoporous silica particles as a silica source and as a sacrificial macroporogen. These novel hierarchical zeolite crystals are expected to reduce diffusion limitations in all zeolite-catalyzed reactions, especially in the transformation of larger molecules like in the catalytic cracking of polymers and the conversion of biomass.

Preparation and Potential Catalytic Applications of Hierarchically Structured Zeolites with Macropores - Weissenberger, Tobias; Machoke, Albert; Reiprich, Bastian; Schwieger, Wilhelm (Advanced Materials Interfaces, 2021)
Hierarchically structured zeolites can mitigate problems arising from the slow transport in the micropores, such as diffusion limitations. Hence, a manifold of different preparation methods for hierarchical zeolites have been developed over the years and the corresponding zeolites showed superior performance due to enhanced mass transport caused by higher diffusivities in the additional pore system and reduced diffusion path length in the micropores. The dimensions of the additional secondary “transport” pores in these materials is a major factor affecting their diffusion properties and consequently their catalytic performance. Interestingly almost all reports focus on the generation of additional mesopores and study of catalytic performance of mesoporous zeolites. Larger macropores with pore diameters of more than 50 nm, however, have some intrinsic advantages over mesopores that make them very attractive for catalytic applications. In the last years, methods for the preparation of zeolites and zeolite composites with additional macropores have been developed. These developments have brought about a novel and promising class of hierarchically structured materials; zeolites with macropores. This review gives an overview about different preparation routes for zeolites with inter or intra crystalline macropores as well as zeolite composites with macropores and summarizes the first studies regarding catalytic their performance.
CRIS-Team Scopus Importer:2021-02-05
Keywords: catalysts; hierarchical zeolites; hierarchically-ordered materials; macropores; zeolites

Scale-Bridging 3D Analysis of Micro-/Macroporous Zeolite Particles Using X-Ray Nano-Tomography and Electron Tomography - Apeleo Zubiri, Benjamin; Weissenberger, Tobias; Przybilla, Thomas; Wirth, Janis; Englisch, Silvan; Drobek, Dominik; Schwieger, Wilhelm; Spiecker, Erdmann (Cambridge University Press, 2019)

Scale-Bridging 3D Analysis of Micro-/Macroporous Zeolite Particles Using X-Ray Nano-Tomography and Electron Tomography - Apeleo Zubiri, Benjamin; Weissenberger, Tobias; Przybilla, Thomas; Wirth, Janis; Englisch, Silvan; Drobek, Dominik; Schwieger, Wilhelm; Spiecker, Erdmann (Microscopy and Microanalysis, 2019)

Scale-up of the Synthesis of Zeolitic Imidazolate Framework ZIF-4 - Hovestadt, Maximilian; Vargas Schmitz, Jürgen; Weissenberger, Tobias; Reif, Florian; Kaspereit, Malte; Schwieger, Wilhelm; Hartmann, Martin (Chemie Ingenieur Technik, 2017)
A new synthesis route for the zeolitic imidazolate framework ZIF-4 is reported. About 200 g of ZIF-4 are prepared by sonothermal synthesis from ZnO at room temperature. The ZIF-4 prepared by sonothermal synthesis is comparable to the ZIF-4 synthesized by the pathway reported in literature with respect to the powder X-ray diffraction pattern, particle size, and separation potential for olefin-paraffin gas mixtures. Moreover, the separation potential of ZIF-4 is compared to commercial adsorbents like carbon molecular sieves and zeolites.
Keywords: Adsorption; Ethylen; Porosity; Ultrasound-assisted synthesis

Synthesis and Catalytic Performance of Aluminium-containing Mesoporous, Spherical Silica Particles - Weissenberger, Tobias; Machoke, Albert; Kolle, Joel M.; Avadhut, Yamini; Hartmann, Martin; Schwieger, Wilhelm (Chemie Ingenieur Technik, 2021)
A one-pot synthesis of aluminium-containing mesoporous silica particles (Al-MSPs) utilizing polyvinyl alcohol (PVA) as steric stabilization agent is reported. PVA prevents particle agglomeration even when the ionic aluminium source is present in the synthesis mixture. Silicon and aluminium sources were utilised completely, resulting in high yield and easy adjustment of the Si/Al ratio. The Al-MSPs showed a spherical morphology, high surface area and were active for the liquid-phase Beckmann rearrangement of cyclohexanone to caprolactam.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Alumina; Beckmann rearrangement; Mesoporous particles; Silica

Synthesis and characterisation of hierarchically structured titanium silicalite-1 zeolites with large intracrystalline macropores - Weissenberger, Tobias; Leonhardt, Rainer; Apeleo Zubiri, Benjamin; Pitínová-Štekrová, Martina; Sheppard, Thomas L; Reiprich, Bastian; Bauer, Jürgen; Dotzel, Ralf; Kahnt, Maik; Schropp, Andreas; Schroer, Christian G; Grunwaldt, J.D.; et al. (Chemistry - A European Journal, 2019)
We report the successful synthesis of hierarchically structured titanium silicalite-1 (TS-1) with large intracrystalline macropores by steam-assisted crystallisation of mesoporous silica particles. The macropore topology was imaged in 3D using electron tomography and synchrotron radiation-based ptychographic X-ray computed tomography, revealing interconnected macropores within the crystals accounting for about 30 % of the particle volume. The study of the macropore formation mechanism revealed that the mesoporous silica particles act as a sacrificial macropore template during the synthesis. Silicon to titanium ratio of the macroporous TS-1 samples was successfully tuned from 100 to 44. The hierarchically structured TS-1 exhibited high activity in the liquid phase epoxidation of 2-octene with hydrogen peroxide. The hierarchically structured TS-1 surpassed a conventional nano-sized TS-1 sample in terms of alkene conversion and showed comparable selectivity to the epoxide. The flexible synthesis route described here can be used to prepare hierarchical zeolites with improved mass transport properties for other selective oxidation reactions. <br